Optimization of Traffic Dikmas by the Kamsel Unit to Prevent Traffic Accidents in the Legal Area of the Tegal Police - Fardi, Farhan (Indonesian Journal of Police Studies, 2024)
Central Java is the province with the highest number of accidents in Indonesia. One of the regencies with the most traffic accidents is Tegal Regency which reached 603 cases of traffic accidents and material losses of Rp 656,600,000. The increasing number of traffic accidents in Tegal Regency, it is the duty of the Traffic Police Unit of Tegal Regency to prevent them by providing guidance and community education in the field of traffic accidents. Therefore, the purpose of this study is to describe the preventive efforts, namely Dikmas Lantas by the Kamsel Unit of the Traffic Police of Tegal to reduce traffic accidents and the factors that cause traffic accidents in the jurisdiction of the Tegal Police. This research was conducted with a qualitative approach and data collection techniques through interviews, observation and documentation studies. The results showed that the Kamsel Satlantas Unit of the Tegal Police Station in the implementation of the Iantas community service has been routinely carried out but there are still many problems and results that are far from expectations. Analysis with management theory for technical planning, organizing, implementing, and controlling is still not optimal due to lack of planning, material that has not been varied, implementation targets that have not covered all schools and private employees. In addition, an analysis using the theory of organizational resources found another problem, namely the ability of the Kamsel Unit which has not participated in vocational education in the community then. Based on the results of the analysis, the researcher suggested a solution to the problem in the implementation of dikmas then by making structured planning and equalization so that it can be implemented in all circles of society, Kamsel Unit that can innovate in preparing and delivering material, increasing the number of Kamsel Unit personnel, improving the quality of Kamsel Unit by dispatching personnel to attend dikmas then vocational education. It is expected that traffic accidents in Tegal Regency can decrease.